Inclusion policies for social minorities in higher education: dialogue between the Brazilian and Nordic contexts - Murilo Anjos; Fillipe de Queiroz; Larissa Porto; Cristiana Kaipper; Vívian Volkmer Pontes; Giuseppina Marsico (Nordic Journal of Studies in Educational Policy)
This article examines the impact of socially constructed meanings regarding social minorities on the development of inclusion policies for these groups in higher education. This analysis is based on a comparative case study between Global South and Global North, specifically focusing on a dialogue between Brazil and Nordic contexts. Social minorities, such as women, the impoverished, black people, LGBTQIA+ people, immigrants and people with disabilities, are more likely to be socially underserved, making them more susceptible to adverse experiences. From this perspective, we analyse the definitions and characteristics currently applied to social minorities and reflect on how these traits function in the field of higher education in order to support student inclusion. Using a theoretical approach from Semiotic Cultural Psychology, we examine the current political landscape and how socially constructed meanings related to these groups influence the development of inclusion policies. These debates reflect an overriding need to reimagine higher education as an arena for inclusion and critical thinking, not only fostering access for social minorities, but also ensuring such debates continue within academia, and, therefore, within society.